Perlindungan Hukum Bagi Saksi Dalam Proses Peradilan Pidana Ditinjau Dari Undang-Undang Nomor 13 Tahun 2006 - Tri Mei Rosalya Purba; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (International Forum of Researchers and Lecturers, 2023)
The position of witnesses in the criminal justice process occupies a key position, as seen in Article 184 of the Criminal Procedure Code (hereinafter abbreviated to KUHAP). The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. In the criminal justice system, witnesses have not been maximally protected in a number of laws and regulations such as in the Criminal Procedure Code and in the Criminal Code, where witnesses have not received maximum attention because in the law above, almost in the articles of the Criminal Procedure Code there is not a single article that specifically regulates witness protection and almost every article in the Criminal Procedure Code and the Criminal Code, witness rights are always included with the rights of victims. The Criminal Procedure Code, which has so far been the basis for proceedings in Indonesian criminal justice, does not regulate the rights and protection of witnesses fundamentally or specifically even though there are several provisions. in the Criminal Procedure Code which regulates, regarding the rights of a witness as Article 108 paragraph (1) reads: every person who experiences, sees and witnesses and/or becomes a victim of an incident which constitutes a criminal act has the right to submit a report or complaint to the investigator or investigator either verbally or verbally. writing.